Law Enforcement Against Parents as Perpetrators Criminal Offense of Baby Dumping in Wonosobo Regency Leksono Sub-District - Cahyani, Mitha Indah; Faustina, Fransisca Okta (UM Purwokerto Press, 2023)
The crime of baby dumping is an act committed by a person who intentionally leaves a newborn baby alive or dead somewhere with the intention of leaving his/her responsibility. Baby dumping is usually committed against children born out of wedlock. It is an act that is contrary to human values. This study aims to determine the law enforcement against parents as perpetrators of criminal acts of baby dumping and to find out what efforts can be made to overcome baby dumping that occurs in Wonosobo Regency, Leksono District. With the formulation of the problem: (1) How is law enforcement against parents as perpetrators of baby dumping in Wonosobo Regency, Leksono Subdistrict? (2) How are efforts to overcome baby dumping in Wonosobo Regency, Leksono Subdistrict? The type of research used by the author is normative juridical research. The approach method used is the statutory approach. The source of data in this research comes from secondary data obtained from reviewing literature studies. The data obtained is analyzed using normative descriptive. The results showed that law enforcement against perpetrators of baby dumping in the jurisdiction of Wonosobo Regency has not gone well, due to the search for perpetrators that takes a long time and with little evidence. The efforts to overcome the obstacles to the occurrence of criminal acts of baby dumping in the jurisdiction of Wonosobo Regency are by instilling moral and formal education, providing counseling, and maximum enforcement of regulations used.